2009
DOI: 10.1172/jci36022
|View full text |Cite
|
Sign up to set email alerts
|

NCRs and DNAM-1 mediate NK cell recognition and lysis of human and mouse melanoma cell lines in vitro and in vivo

Abstract: NK cells use a variety of receptors to detect abnormal cells, including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
308
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(316 citation statements)
references
References 36 publications
5
308
0
3
Order By: Relevance
“…Alternatively, it is also possible that NKp46/NCR1 inhibits metastases detachment from the primary tumors, or that it kills the disseminating metastases on their way to the lungs. Additionally, it is possible that the location of the primary tumors is important, as in previous models the cancer cells were s.c. injected into the flank and NK cells migrated to these tumors (12)(13)(14), whereas here tumor cells were injected into the footpad to enable spontaneous metastasis. Finally, it is possible that the circulating tumor cells transiently changed their properties during their migration to the lungs and that this is NCR1-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, it is also possible that NKp46/NCR1 inhibits metastases detachment from the primary tumors, or that it kills the disseminating metastases on their way to the lungs. Additionally, it is possible that the location of the primary tumors is important, as in previous models the cancer cells were s.c. injected into the flank and NK cells migrated to these tumors (12)(13)(14), whereas here tumor cells were injected into the footpad to enable spontaneous metastasis. Finally, it is possible that the circulating tumor cells transiently changed their properties during their migration to the lungs and that this is NCR1-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NKp46/NCR1 by its unknown tumor ligand(s) can lead either to IFN-g secretion (14), to enhanced killing, or to both (7,8,12). To test which of these mechanisms is activated when NK cells interact with B16 or D122 cells we used the NCR1 gfp/gfp (KO) and the immune competent NCR1 +/gfp (Het) mice, (7), in a CD107a (LAMP-1) mobilization assay (16).…”
Section: Nkp46/ncr1-dependent Nk Degranulation Following Incubation Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that intrahepatic frequency of NKp46 High NK cells inversely correlated with HCV loads. Whether NKp46 recognizes a HCV-derived protein [17][18][19][20][21] or interacts with a yet unknown NKp46 ligand, as has been suggested for malignant transformed cells, 40,41 remains to be clarified. However, blocking of NKp46 significantly reduced the capability of both circulating and intrahepatic NK cells to block HCV replication, suggesting a role of NKp46 in the regulation of anti-HCV immune responses.…”
Section: Nk Cells (Supportingmentioning
confidence: 99%
“…19 Indeed, DNAM-1 triggers NK cell killing of freshly isolated ovarian carcinoma and neuroblastoma cells 20,21 and is required for killing and control of melanoma metastases. 22,23 Similarly, mice lacking DNAM-1 exhibit accelerated growth of DNAM-1 ligandexpressing tumors. 24 Thus, DNAM-1 appears to be a key regulator of NK-cell-mediated cancer immunosurveilance.…”
Section: Introductionmentioning
confidence: 99%